2016
DOI: 10.1115/1.4034041
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Single-Jet Combustor Near Lean Blowout Conditions Using Flamelet-Generated Manifold Combustion Model and Detailed Chemistry

Abstract: Numerical simulation results of a single-jet premixed combustion system at atmospheric pressure are compared against comprehensive particle image velocimetry (PIV) flow measurements and Raman scattering temperature measurements for natural gas and hydrogen fuels. The simulations were performed on hexahedral meshes with 1–5 × 106 elements. Reynolds-averaged Navier–Stokes (RANS) calculations were carried out with the k–ε realizable turbulence model. Combustion was modeled using the flamelet-generated manifold mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Zghal et al [6] applied the FGM and EDC to model a hydrogen-fueled micromix burner and concluded that both FGM and EDC can capture the features of micro-mix flame well. Patil et al [8] compared the performance of EDC and FGM in evaluating a CH4-fuelled single-jet flame near lean blowout conditions; the study confirmed that EDC yielded closer agreement with measured results than FGM in capturing lean flame behaviours, as shown in Figure 1. This figure shows that with increasing centerline distance away from the jet flame, the FGM model generally poorly predicts the temperature profiles, compared to the EDC.…”
Section: Rang Zhaomentioning
confidence: 79%
See 1 more Smart Citation
“…Zghal et al [6] applied the FGM and EDC to model a hydrogen-fueled micromix burner and concluded that both FGM and EDC can capture the features of micro-mix flame well. Patil et al [8] compared the performance of EDC and FGM in evaluating a CH4-fuelled single-jet flame near lean blowout conditions; the study confirmed that EDC yielded closer agreement with measured results than FGM in capturing lean flame behaviours, as shown in Figure 1. This figure shows that with increasing centerline distance away from the jet flame, the FGM model generally poorly predicts the temperature profiles, compared to the EDC.…”
Section: Rang Zhaomentioning
confidence: 79%
“…The GRI-mech3.0 [25] is a chemistry kinetic mechanism widely used to model natural gas flames. Its use in CFD is proposed by several works including Refs [8][10] [26]. When modelling the co-firing of CH4/H2 blends, it is generally recommended to use the GRI-3.0 chemical kinetic mechanism for low hydrogen concentrations (<50%).…”
Section: Turbulence and Combustion Modelsmentioning
confidence: 99%